Executive Control of Walking in People With Parkinson's Disease With Freezing of Gait. (December 2020) - Vitorio, Rodrigo; Stuart, Samuel; Mancini, Martina
Background: Walking abnormalities in people with Parkinson's disease (PD) are characterized by a shift in locomotor control from healthy automaticity to compensatory prefrontal executive control. Indirect measures of automaticity of walking (eg, step-to-step variability and dual-task cost) suggest that freezing of gait (FoG) may be associated with reduced automaticity of walking. However, the influence of FoG status on actual prefrontal cortex (PFC) activity during walking remains unclear. Objective: To investigate the influence of FoG status on automaticity of walking in people with PD. Methods: Forty-seven people with PD were distributed into 2 groups based on FoG status, which was assessed by the New Freezing of Gait Questionnaire: PD−FoG (n = 23; UPDRS-III = 35) and PD+FoG (n = 24; UPDRS-III = 43.1). Participants walked over a 9-m straight path (with a 180° turn at each end) for 80 seconds. Two conditions were tested off medication: single- and dual-task walking (ie, with a concomitant cognitive task). A portable functional near-infrared spectroscopy system recorded PFC activity while walking (including turns). Wearable inertial sensors were used to calculate spatiotemporal gait parameters. Results: PD+FoG had greater PFC activation during both single and dual-task walking than PD−FoG ( P = .031). There were no differences in gait between PD−FoG and PD+FoG. Both groups decreased gait speed ( P = .029) and stride length ( P < .001) during dual-task walking compared with single-task walking. Conclusions: These findings suggest that PD+FoG have reduced automaticity of walking, even in absence of FoG episodes. PFC activity while walking seems to be more sensitive than gait measures in identifying reduction in automaticity of walking in PD+FoG.